Prevalensi cendawan entomopatogenik, Neozygites fumosa (Speare) Remaudie’re & Keller (Zygomycetes: Entomophthorales) pada populasi kutu putih, Paracoccus marginatus Williams & Granara De Willink (Hemiptera: Pseudococcidae) di wilayah Bogor - Anik Nurhayati; Ruly Anwar (Perhimpunan Entomologi Indonesia, 2012)
The prevalence of entomopathogenic fungus, Neozygites fumosa (Zygomycetes: Entomo-phthorales) on the papaya mealybug, Paracoccus marginatus (Hemiptera: Pseudococcidae), was studied in Bogor in two districts: Bubulak and Rancabungur in 2011. Thirty plants of either papaya or cassavas were sampled 8 times, once a week for insect population and biweekly for the fungus infection sampling. The results showed that the cassava mealybug was not found on both plants and all locations. The populations of papaya mealybug in Bubulak were higher than in Rancabungur. The populations of papaya mealybug on papaya were higher than those of cassava. However, N. fumosa infection levels on both plants and both locations were not significantly different.